2013
DOI: 10.1007/s11695-013-1091-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Electrical Neurostimulation of Dermatome T6 for Appetite Reduction and Weight Loss in Morbidly Obese Patients

Abstract: PENS of dermatome T6 was associated with appetite reduction in all of the patients and, along with a proper diet, achieved a significantly greater weight reduction than diet alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Based on these assumptions, non-invasive VNS was supposed as a treatment option for obesity ( Page et al, 2012 ). First findings indeed suggest a reduction in appetite and body weight ( Ruiz-Tovar et al, 2014 ; Ruiz-Tovar and Llavero, 2016 ) (see Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on these assumptions, non-invasive VNS was supposed as a treatment option for obesity ( Page et al, 2012 ). First findings indeed suggest a reduction in appetite and body weight ( Ruiz-Tovar et al, 2014 ; Ruiz-Tovar and Llavero, 2016 ) (see Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 84%
“…In a well-controlled proof-of-concept study, Ruiz-Tovar et al (2014) found in 45 mainly female, obese individuals that diet in combination with non-invasive VNS delivered to the T6 dermatome led to reductions of body weight and appetite. In a follow-up study they also evaluated the long-term effect of non-invasive VNS.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, PENS of dermatome T6 has been proposed as an alternative to pharmacological products and surgical procedures to decrease appetite and weight loss, allowing a better compliance of hypocaloric diets. PENS was initially applied to morbidly obese patients awaiting bariatric surgery, in order to reduce the pre-surgery body weight [ 10 ]. Later, we and others extended this technique to patients with overweight and mild-to-moderate obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The PENS of dermatome T6 was performed as previously described [ 10 ] by using the Urgent PC 200 Neuromodulation System ® (Uroplasty, Minnetonka, MN, USA). Patients were placed in a supine position without anesthesia, and PENS was delivered by a needle electrode inserted in the left upper quadrant along the medio-clavicular line, at two centimeters below the ribcage, at a 90° angle towards the abdominal wall, and at 0.5–1 cm of depth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation